Being real : the student-teacher relationship and African-American male delinquency - Gibson, Camille, 1971- (Criminal justice (LFB Scholarly Publishing LLC), 2002)
Gibson examines the role of school teachers in helping African-American juveniles not only to learn but also to acquire the social and cultural skills to avoid delinquency and attain upward social mobility. Gibson looks at how student-teacher relationships affect African American males. She studied students in two Bronx, New York, schools. African-American males may start optimistic, but they often come to perceive school as a poor option for achieving the "American dream." Instead, they may turn to crime, most often drug dealing and violence. Gibson's work shows how teachers affect this process. Teachers are most effective when they are "real": caring and willing to share of themselves as they pass on not only the subject matter of the class but also the social and cultural capital necessary to maximize their students chances at upward social mobility